Analisis Faktor Penyebab Kesulitan Belajar dalam Pembelajaran Bahasa Indonesia di Sekolah Dasar - Fajari, Laksmi Evasufi Widi (LPPM Universitas Bina Bangsa, 2025)
The aim of this study is to analyze learning difficulties experienced by fifth-grade elementary school students. This research employs a qualitative case study approach and was conducted at SD Negeri Serang 8. The research subjects consisted of fifth-grade teachers and students selected through purposive sampling. Data were collected using observation, interviews, and documentation techniques. The analysis involved three stages: data reduction, data presentation, and drawing conclusions. The findings revealed two main factors: (1) internal factors, including physiological and psychological aspects. Physiological issues such as fatigue and illness contributed to learning difficulties in the four language skills. Psychological issues included lack of interest in reading and low intelligence, which negatively affected students’ language learning. (2) External factors included the school environment, family environment, and community environment. At school, the teacher’s role significantly impacted students’ difficulties in the four language skills. In the family environment, the lack of early writing habits fostered by parents was a contributing factor. In the community environment, negative surroundings, such as peer influence and neighborhood conditions, also affected students. The study concludes that fifth-grade students’ learning difficulties in the four language skills are influenced by both internal and external factors.